N-(2-methoxyethyl)phthalimide - Ariffin, Azhar; Ng, S.W.; Sim, Y.L. (International Union of Crystallography, 2008)
The title molecule, C11H11NO3, lies on a crystallographic mirror plane which bisects the plane of the phthalimide unit and contains the C and O atoms of the 2-methoxyethyl group.